Impeachment and Its Problem: The Study from Constitutional Law vs Criminal law Perspective in Indonesia - Sujatnika, Ghunarsa; Ghozi, Ahmad; Satriya, Catur Alfath (Revista de Investigações Constitucionais, 2024)
This paper will discuss the problems of the impeachment process in Indonesia. This issue focus on Articles 7A and 7B of the 1945 Indonesian Constitution. The two articles regulate the reasons for the impeachment process for the President and/or Vice President. This paper highlights two points. First is the impeachment process in Indonesia. Second, regarding the issue of the impeachment process being carried out, whether it can be a reason to abolish the prosecutor’s authority in prosecuting in the case of ne bis in idem or not. This research uses conceptual and historical approaches to analyze the problems discussed. From this study, the authors found that there are still problems in the legal aspect of evidence in the impeachment process, which still opens the possibility of the person being tried in another judicial system. Another finding is that the impeachment process and criminal/civil justice generally have different objects so that a person can be tried again. However, it needs to be strictly regulated in regulations related to the process and post-impeachment so that it no longer creates many interpretations in its implementation.